Data Deletion and Recovery of Androd Plaforms - Kim, Hyungchan; Shin, Yeonghun; Kim, Sungbum; Kim, Minju; Jo, Wooyeon; Shon, Taeshik (Proceedings - 2021 International Conference on Computational Science and Computational Intelligence, CSCI 2021, 2021)
The Android platform accounts for 83% of the global smartphone operating system market share. Android smartphones store personal information and smartphone usage data. In order to prevent cyber security threats, it is important to manage data stored in Android smartphones. In this paper, we analyze the deleted data and recovery possibilities remaining in smartphones using Android 9 and 10. The deleted data recoverability analysis is performed based on the scenario of deleting data using the app's own features. We confirmed that deleted data can be recovered from the android messenger application. This paper result is expected to be applicable to IoT devices based on Android platform and we found that sustained research on Android platform should be conducted from the perspective of forensics.
Keywords: Android filesystem; Android forensics; Android platforms; Android smartphone; Cyber security; Filesystem; Market share; Personal information; Smart phones; Usage data; Android filesystem; Android Forensic; Digital Forensic